PENGARUH DISIPLIN KERJA, MOTIVASI KERJA TERHADAP KEPUASAN KERJA DAN DAMPAKNYA TERHADAP KINERJA KARYAWAN DIVISI VENDOR MANAGEMENT PT ASURANSI JIWA MANULIFE INDONESIA , JAKARTA SELATAN - Yolanda Yolanda; Fitra Dwi Mawarti (Fakultas Ekonomi Universitas Borobudur, 2019)
This study aims to examine and analyze the Effect of Work Discipline, Work Motivation on Job Satisfactionand Its Impact on Employee Performance.The data used in this study are primary data taken from questionnaire responses by the Vendor ManagementDivision Employees. The data processing method uses the path analysis method with the help of SPSS analysis toolversion 24. The statistical testing in this study uses a model of goodness of fit test.The results showed that Work Discipline had a positive and significant effect directly or indirectly throughwork motivation on job satisfaction, employee performance.Keywords: Work discipline, work motivation, job satisfaction, employee performance.